1037 A cross-sectional study to validate a screening questionnaire to determine prevalence of work-related asthma in primary health care in chile. (24th April 2018) - Solar, O; Contreras, G; Sepulveda, R; Castillo, S
Abstract : Introduction: The attributable population risk of work-related asthma is between 10% and 20% of total cases of asthma. In Chile, the prevalence of common asthma is 10.2% but the proportion of occupational asthma (OA) is hidden and invisible. The study objective was to determine the prevalence of OA among asthmatic patients in regular control in the Primary Health Care (PHC) adult respiratory diseases program in Santiago, Chile. Methods: A descriptive, cross-sectional multicenter study of patients aged 20 to 64 years with diagnosis of asthma, according to medical records and functional respiratory tests; who were working or had worked and were in control in PHC in a healthcare district of Santiago. An Occupational Asthma Screening Questionnaire (OAS) was developed and validated in four PHC centres to identify occupational asthma in the population in control for bronchial asthma. The screening instrument included six questions with a scale from 6 to 16 points. The instrument was prepared with a panel of experts with validation of feasibility, reliability, logic, content, construct and criteria, using confirmatory diagnostic tests and blind medical evaluation by two specialists in respiratory diseases and occupational medicine as the gold standard. Patients were classified into three categories: OA, work-exacerbated asthma WEA or common asthma (CA), according to OAS and the medical evaluation. Result: Two hundred and two patient completed the OAS and were evaluated by specialists. A cut-off of >10.5, points in the OAS yielded sensitivity of 0.79; specificity of 0.78; VP (+) 0.22 and VP (-) 0.98. The detected prevalence of OA was 8.2% and asthma exacerbated by work was 14.2%, for a total prevalence of work-related asthma of 22%. Discussion: The findings support implementation of an occupational asthma surveillance program in the PHC network in Santiago, Chile to benefit workers and to improve the results of PHC respiratory health programs.